Analysis of operation characteristics of junctionless poly-Si 1T-DRAM in accumulation mode. (9th September 2019) - Kim, Hyeonjeong; Kang, In Man; Cho, Seongjae; Sun, Wookyung; Shin, Hyungsoon
Abstract: Capacitorless DRAM (1T-DRAM) is considered to be a promising candidate to replace conventional 1T-1C DRAM which is facing a scaling limit. 1T-DRAM with a poly-Si body has attracted much attention specifically for its simple SOI fabrication and stackable memory which allow for ultrahigh density. A single crystal silicon-based junctionless (JL) transistor is unsuitable for a 1T-DRAM cell because the transistor's body is too thin to have a storage region and its junction barrier is too low to store holes. In contrast, a JL transistor with a thin poly-Si body can be used as a 1T-DRAM cell because it uses a grain boundary as its charge storage region instead of a floating body. We carried out intensive simulations of JL transistors with poly-Si body and confirmed the possibility of using a JL structure as a poly-Si 1T-DRAM cell. In addition, we analyzed the memory mechanism and characteristics of this structure.